Prevention Of Suicide Through Character and Identity Strengthening At the Digital Era In Lombok Community - Wirawan, I Wayan Ardhi; Gelgel, I Putu; Widana, I Nyoman Murba; Sarjana, I Putu; Hadriani, Luh Gde; Mahardika, Gede (IAHN Gde Pudja Mataram, 2025)
This article aims to prevent suicide cases in the Lombok community in the digital era by strengthening character and identity through Community Service Activities which is hereinafter abbreviated as CSA. The methods used include workshop digital literacy education, character building training, and community activities based on reflections on religious cultural values. This activity has used training methods, workshops, and community activities. The results of the CSA Program indicate an increase in community understanding of suicide risk factors, understanding values of building character, self-confidence, and a sense of togetherness through community activities. The CSA Program activities also encourage the formation of community support networks that are more responsive to mental health issues. In conclusion, an integrative approach between digital literacy, religious cultural values, and character building is expected to be effective in increasing psychological resilience and preventing suicide risk in the Lombok community. These CSA activities can be expected to become an adaptive community-based intervention model for strengthening character and identity amidst the dynamics of the digital era.